Las competencias del comunicador en el contexto post pandemia. Estudio de la Zona 5 del Ecuador - Bazurto Rodríguez, Edson Jeampier (2022)
This case study determined the competencies of the communicator in the post-pandemic context of zone 5 of Ecuador, taking as a reference the universities, since, communicators are graduating every semester being part of the province of Los Ríos, Bolívar, Galápagos, Santa Elena and Guayas; except for the cantons (Guayaquil, Duran and Samborondón). It was possible to recognize the new work scenarios, identifying the knowledge, skills, aptitudes and prospective scenarios for the communicator after the pandemic. The methodology used was quali-quantitative and through the instrument of the interview we dialogued with communicators graduated before the pandemic, graduates after the pandemic, with owners of traditional media such as television, with university professors of the communication career; they manifested similar situations, the one that stands out the most is the innovation of information and having knowledge in audiovisual editing. To obtain data and documented information, we resorted to the bibliographic review of past research up to five years old. 169 communicators from the five provinces were surveyed As consolidated results it was obtained that the competences of communicators are acquired in the different stages of life as a communicator, who must inform in a clear, simple and concrete way, in addition, explore other areas of the communication field, move away from radical and technological changes, generate trust and above all, be a todologist communicator; that's the main competition